Transformasi Program Sosial Keagamaan melalui Pendampingan Manajemen Dakwah Humanis pada PC Muslimat NU Nganjuk - Diana Elfiyatul Afifah; Nandipah Roa’zah; Muslimatun Diana Muazaroh (Universitas Pangeran Diponegoro Nganjuk, 2026)
The transformation of religious social programs has become an urgent need amid the social dynamics of society and the increasing complexity of family and religious issues at the local level. This community service focuses on assisting the management of humanistic da'wah at PC Muslimat NU in Nganjuk Regency with the aim of strengthening program management to be more focused, collaborative, and impactful. The activity was carried out in early September 2025 using a participatory action research (PAR) approach through the stages of situation analysis, participatory planning, management workshops, guided implementation, and reflective evaluation. The results of the community service showed structural changes in the form of the preparation of integrated work plans and program evaluation indicators, cultural changes in collaborative work patterns, and the strengthening of women's participatory leadership. The integration of humanistic values and professional management systems has proven to encourage the sustainability of religious social programs as instruments of social transformation based on women's organizations.